A Case of Opsoclonus-Myoclonus-Ataxia With Neuronal Intermediate Filament IgG Detected in Cerebrospinal Fluid. Issue 2 (June 2022) - Merati, Melody; Rucker, Janet C.; McKeon, Andrew; Frucht, Steven J.; Hu, Jessica; Balcer, Laura J.; Galetta, Steven L.
Abstract : Supplemental Digital Content is Available in the Text. Abstract: A 62-year-old man presented with headache, fever, and malaise. He was diagnosed with Anaplasma phagocytophilum, confirmed by serum polymerase chain reaction, and started on oral doxycycline. After 5 days of treatment, the patient began to experience gait imbalance with frequent falls, as well as myoclonus, and confusion. Examination was notable for opsoclonus-myoclonus-ataxia (OMA) and hypometric saccades. Cerebrospinal fluid (CSF) autoimmune encephalitis panel demonstrated a markedly elevated neuronal intermediate filament (NIF) immunoglobulin G antibody titer of 1:16, with positive neurofilament light- and heavy-chain antibodies. These antibodies were suspected to have been triggered by the Anaplasma infection. Repeat CSF examination 8 days later still showed a positive immunofluorescence assay for NIF antibodies, but the CSF titer was now less than 1:2. Body computed tomography imaging was unrevealing for an underlying cancer. Our patient illustrates a postinfectious mechanism for OMA and saccadic hypometria after Anaplasma infection.